Pengaruh Suhu Penyimpanan pada Gabah Basah yang Baru Dipanen terhadap Perubahan Mutu Fisik Beras Giling - Tanwirul Millati; Yudi Pranoto; Nursigit Bintoro; Tyas Utami (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2017)
Rice storage on high moisture content and temperatures could accelerate aging process. This research studied the effect of temperature and storage time to changes in the milling quality and color of the milled rice. This study used freshly harvested rough rice of IR 64 varieties with a moisture content of 26.73%, storage temperatures consist of room temperature, 40 °C, 50 °C and 60 °C, and storage time of 0, 2, 4, 6, 8, and 10 days. Observations comprise weight loss and a decrease in grain moisture content, and color quality milled rice. The results showed that the temperature and storage time affects weight loss and decrease moisture content of rough rice, milling quality, and color of the milled rice. The higher temperature and the longer storage, the weight loss and the decreasing moisture content of rough rice increases. Freshly harvested rough rice storage at 40 °C after 6 days showed a relatively large weight loss due to damage of rough rice. The yield and quality of milled rice increased with storage time. Rice color was relatively fixed until the 10th days at room temperature and 40 °C, while stored at 50 °C and 60 °C, the yellowing started after the 4th day and 2nd day respectively. Based on SNI 6128: 2008, water content of milled rice entered the category of quality I, head rice yield on category II and III, while the broken grains and grain groats entered in category II, III, and IV. Temperature and storage time recommended for the storage of freshly harvested rough rice was at 40 °C for 6 days. ABSTRAKSelama penyimpanan gabah terjadi proses pengusangan yang akan mengubah mutu giling dan warna beras. Penyimpanan gabah pada kadar air dan suhu tinggi dapat mempecepat proses penurunan mutu. Penelitian ini mempelajari pengaruh suhu dan lama penyimpanan terhadap kehilangan berat dan penurunan kadar air gabah, perubahan mutu giling dan warna beras selama penyimpanan gabah kering panen. Suhu penyimpanan yang digunakan adalah suhu ruang, 40 °C, 50 °C, dan 60 °C, sedang lama penyimpanan adalah 0, 2, 4, 6, 8, dan 10 hari. Suhu dan lama penyimpanan mempengaruhi kehilangan berat dan penurunan kadar air gabah, mutu giling dan warna beras. Semakin tinggi suhu dan semakin lama penyimpanan, kehilangan berat dan penurunan kadar air gabah semakin besar. Penyimpanan gabah pada suhu 40 °C setelah 6 hari menunjukkan kehilangan berat yang relatif besar, meskipun terjadi peningkatan rendemen dan mutu giling. Berdasarkan SNI 6128:2008, kadar air beras giling masuk pada katagori mutu I, persentase beras kepala masuk pada katagori mutu II dan III, sedangkan butir patah dan butir menir masuk pada katagori mutu II, III, dan IV. Warna beras relatif tetap sampai 10 hari penyimpanan pada suhu ruang dan pada 40 °C, sedang pada suhu 50 °C mulai terjadi penguningan setelah penyimpanan 4 hari dan pada suhu 60 °C setelah 2 hari. Suhu dan lama penyimpanan yang direkomendasikan untuk penyimpanan gabah kering panen adalah pada suhu 40 °C selama 6 hari.